INTEGRASI MEDIASI KASUS PERCERAIAN DALAM BERACARA DI PENGADILAN AGAMA - Muhammad Saifullah (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2014)
This research aims to determine the implementation of mediation in divorce cases in The Religion Court Semarang, the substance perspective for PerMA No. 1 of 2008 on Mediation Procedure in the Court, and the legal culture for citizen proposing their problem to the court. This study uses the non-doctrinal law approach that puts the law as